Investigating the relationship between kimberlites and large low shear velocity provinces over the African continent - Nechi, Vivian Onyinye (My University, 2026)
Kimberlites are relatively rare ultramafic igneous rocks commonly emplaced on Archean cratons. They are widely distributed, and several hypotheses have been proposed to explain their emplacement. In this study, we provide new constraints on the African kimberlites’ emplacement by backtracking their locations using the free GPlately software, as well as a kinematic model that allows us to go as far back as 1,800 Myr. By considering several new, state-of-the-art tomography models, we quantitatively assess the correlation between Large Low Shear Velocity Provinces (LLSVPs) and backtracked kimberlite locations. Most kimberlites emplaced over the African continent were generated during the 260-0 Myr period (~59%). During this period, most of the kimberlites were generated on the African LLSVPs or along their margins. Our results indicated that the African LLSVPs have remained stable for at least 260 Myr. In contrast, kimberlites older than 260 Ma are mostly not associated with LLSVPs. More precisely, kimberlites emplaced between 590 and 490 Myr show no association with LLSVPs, presenting an intriguing pattern, as the present-day locations of these kimberlites seem to define a NE-SW alignment. We consider constraints from lithosphere-asthenosphere boundary (LAB) and rifting to see if they can account for the kimberlite within this interval. Indeed, our results show that edge-driven convection (EDC) may have played a role in the emplacement of some kimberlite clusters, but there is no clear indication of that for kimberlites emplaced between 590 and 490 Myr. In addition, we show that the comparison between rift and present-day location of kimberlites suggests that the African kimberlites generally emplaced far away from rifts, thus negating the rift’s influence on their emplacement. However, rifts may have helped the emplacement of kimberlites with ages between 590 and 490 Myr.
Keywords: Kimberlites; Large low shear velocity provinces; Plate reconstruction; Seismic tomography